Business Development Strategy through Blue Ocean Strategy in Increasing Product Competitiveness in Gayo Coffee Farming in Aceh: Sharia Business Perspective - Samrin Samrin; Azhari Akmal Tarigan; Sugianto Sugianto (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose: This study examines the role of Blue Ocean Strategy in enhancing product competitiveness in coffee agribusiness from a sharia business perspective. The study is motivated by the need to improve competitiveness and farmer welfare through value innovation, fair business practices, and stronger market positioning. Design/methodology/approach: This study applies a quantitative field research approach with an explanatory design. Data were analyzed using SEM-PLS with SmartPLS 3.0 to examine the relationships among price, distribution channels, product quality, Blue Ocean Strategy, and product competitiveness. Findings/Results: The results show that price and product quality have a significant effect on Blue Ocean Strategy, but do not directly affect product competitiveness. Distribution channels do not have a significant effect on either Blue Ocean Strategy or product competitiveness. Blue Ocean Strategy has a significant positive effect on product competitiveness and mediates the relationship between price and competitiveness as well as between product quality and competitiveness. Originality/Value: This study highlights Blue Ocean Strategy as an important mechanism for improving competitiveness in coffee agribusiness from a sharia business perspective. The findings imply that competitiveness can be strengthened through value innovation, quality improvement, direct selling, digital promotion, and the reduction of exploitative and inefficient business practices.